Penerapan Sistem Keuangan Desa (siskeudes) dalam Pengelolaan Keuangan Desa - Rivan, Arif; Maksum, Irfan Ridwan (Universitas Medan Area, 2019)
The enactment of Law number 6 of 2014 concerning Villages, villages are given the mandate to take care of governance and the implementation of development in the village. The amount of funding provided by the central government to the village to manage all the potential that exists in the village in order to improve the economy and community welfare, the implementation of village financial management must be based on the principle of transparency, accountability, participation, order and budget discipline. To create clean, transparent, accountable, effective and efficient village financial governance, the Financial and Development Supervisory Agency (BPKP) and the Directorate General of Village Government Ministry of Home Affairs collaborate to make an application called the Village Financial System (Siskeudes) for village financial management. This aims to help village governments be more independent in managing village finances effectively and efficiently, as well as increasing transparency in village financial accountability. The factors that influence village financial management such as leadership, human resources, commitment and communication.